Organizational and Rewards as Predictors of Work Engagement at PT Jasa Armada Indonesia TBK - Koko kunaedi; Kartono; Sunimah (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to examine the role of organizational justice and reward as predictors of work engagement at PT Jasa Armada Indonesia Tbk. The study employed a quantitative approach using purposive sampling involving 100 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that organizational justice positively and significantly affects employee work engagement. Reward also serve as a significant positive predictors of work engagement. The results imply that organizations need to improve fairness in organizational practices and implement transparent and performance based reward systems to increase employee engagement and organizational performance